Innovation in the Service Sector: A Possible Recipe for Success for the Spa Towns of Central Europe - Nóra Rodek; Tivadar Máhr; Zoltán Birkner (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
To achieve a competitive advantage, innovation, which provides the possibility to meet the customers' needs a new and higher level, is inevitable for companies. Resources providing the basis of economic development are not widely available and cannot be easily replaced; therefore, expansion of trends focusing on innovation is unavoidable. In the past decade, service sector offered the most knowledge-intensive jobs in the most developed countries of the world. The utilization of research and development results becomes more and more intense that is accompanied by the need that the decision-makers and the actors of the service sector shall have adequate information at disposal. Water is the gold of modern age, and thermal water has been the basis of thermal culture (and business) since ancient times. The Central European region is abundant in thermal water; therefore, the exploitation of such resource is a logical step. In the past decades, developments based on thermal water were carried out in the region. Nowadays, however, it is clear that innovation takes the central role of successful operation in this sector, too. This paper examines the innovation-centred services of spa towns by highlighting on the theoretical background and the necessity for the successful business operation.
Keywords: O3; O35; 330; innovation; services; SPA towns; management of tourism